Organisational culture vs. change management process in higher education institutions: Context of a developing country - Javaid, Sana; Noshaba, Anam; Amjad, Amjad Islam; Aslam, Sarfraz; Almulla, Abdullah Ahmed (International Journal of Innovative Research and Scientific Studies, 2025)
This qualitative research study deeply explores the impact of organizational culture within higher education institutions (HEIs) on change management processes. The research is guided by the influence of organizational culture on the success of change management initiatives in these unique settings. The research design was phenomenology. The participants were individuals involved in change management processes in various HEIs of Pakistan, encompassing administrators and faculty members. The respondents were selected using a purposive sampling technique. A semi-structured interview protocol was developed to collect data through open-ended discussions on cultural elements, values, norms, and beliefs that either facilitate or hinder the success of change management initiatives in HEIs. The interviews were recorded, transcribed, organized, and analyzed systematically. Using thematic analysis, we identified the recurrent themes and patterns influencing the organizational culture in the change management process. Instead of having different challenges, culture plays a significant role in the change management process and is also a significant part of it. Sometimes resistance should be managed, and at times ignored. This research seeks to understand the dynamic interplay between change management processes at HEIs and their culture. It offers practical implications for administrators and faculty members seeking guidance to navigate change challenges in educational settings.